Penerapan Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Materi Menghindari Perilaku Tercela pada Siswa Kelas XI MA Darul Amanah - naili, Naili Faizatur Rohmah; Mustafidin, Ahmad; Maskur; Panuntun, Slamet; Choirudin, Moch (EDUCATIVA, 2025)
Based on the results of the daily assessment in the subject of Akidah Akhlak for Grade XI students at MA Darul Amanah Bedono in the even semester of the 2024/2025 academic year, only 2 out of 7 students (28.57%) achieved scores above the Minimum Mastery Criteria (KKM), while 5 students (71.43%) still received low scores. This outcome indicates that the learning process has not been effective and has not met the expected minimum competency targets. Furthermore, the low learning outcomes are also reflected in student behavior at school, which still shows a lack of application of commendable morals, such as insufficient respect for teachers, low concern for peers, and lack of participation in religious activities. This suggests that students' understanding of Akidah Akhlak is not only weak cognitively but is also not reflected in their daily attitudes and behavior.This study aims to improve student learning outcomes in the subject of Akidah Akhlak with the material "Avoiding Reprehensible Behavior" through the Problem Based Learning (PBL) method in class XI MA Darul Amanah Bedono in the even semester of the 2024/2025 academic year. The method used is Classroom Action Research (CAR) in two cycles with 7 students as subjects. In the pre-cycle, only 2 students (28.57%) completed with an average score of 60.86. After the implementation of PBL, the results increased in cycle I with 4 students (57.1%) completing and an average score of 75.29, and reaching 100% completion in cycle II with an average score of 81.29. In addition to increasing grades, PBL also has a positive impact on student attitudes, such as critical thinking, cooperation, and responsibility, through contextual learning related to tadbzir and bungling behavior. This approach has proven effective in shaping Islamic character and increasing active student involvement